MOTIVASI DIGITAL NOMAD BERKUNJUNG PADA ERA PANDEMI COVID-19 DI KEROBOKAN, BALI - Yuki Sofia; Putu Eka Wirawan; Febianti; Komang Trisna Pratiwi Arcana (UHN IGB Sugriwa Denpasar, 2023)
Digital nomads are classified as nomadic tourists and are individuals who are not tired of moving or traveling to explore new places, but still carry out their daily routines that rely on technology to work. Nowadays, digital nomads are very numerous in all tourism areas because of the increasingly modern era, namely the maximum use of technology and all digital. This study uses quantitative descriptive analysis, which is a method that aims to examine a situation objectively using numbers, starting from collecting data, interpreting the data as well as the appearance and results. The research was conducted from April 17, 2022 to May 7, 2022 for 3 weeks. The target population in this study were digital nomads in Kerobokan, Bali during the Covid-19 pandemic era. The data for this study is data about the motivation of digital nomads to visit Kerobokan, Bali, the data was collected by using a questionnaire and obtained as many as 31 respondents with accidental sampling technique which means that the sample is found or who is suitable as a sample according to the sample criteria. The collected data were analyzed using confirmatory factor analysis. The results showed that 4 new factors were formed that motivated digital nomads to Kerobokan, Bali in the era of the Covid-19 pandemic. The results of this study can later become a new reference in the field of digital nomad motivation factor analysis and as a recommendation or suggestion for future research.